ANALISA ERGONOMI BERDASARKAN PRAKTIKUM LABORATORIUM DI TEKNIK INDUSTRI–USAHID DAN PENERAPAN ERGONOMI DI INDUSTRI GARMENT “AB” - Sukamdani, Haryadi B; Kusnadi, Endang; Sulistyadi, Kohar (JURNAL GAUNG INFORMATIKA, 2016)
This journal is intended to apply laboratory research on an industrial scale that aims to: 1) identify potential workplace accidents, and 2) Implementation of ergonomics in the garment industry to increase productivity of workers and reduce occupational accidents. Therefore, in the methodology, non-experimental and observational research is conducted by observation of a number of subject variables based on the actual state (in nature), without any manipulation or intervention of the researcher, as this research approach used modeling system and simulation study where data, and the role that is displayed in the picture is translated in mathematics from a reality. The end result of this research 1) Identification of work accident potential can be divided into: a. Initial stage can be identified the initial condition, where the condition of the foot is burdened with body weight and unstable position during work back position many curved due to back aches and pains and Adverse effects for internal organs. b. Phase Improvement of observation after improvement of sitting position where in sitting position and standing position, sitting position where the foot is not burdened with body weight and stable position during work. While standing position where vertical vertical position and weight are balanced in two legs. Application in the industry for comparison of seated and standing working positions In the Garment Industry Seated and standing positions have biomechanical advantages, where the pressure on the spine and waist is 30% lower than the sitting position or standing position continuously. 2) The results of ergonomic application in the workplace / garment industry can increase the productivity of the workers: In the implementation of ergonomics, the initial improvement phase in the garment industry obtained a productivity increase of 28%; decreased cruelty; provide work convenience; reduced complaints against occupational health problems and increased worker income by 15% - 17%;